Hundreds of suicidal teens sleep in emergency rooms. Every night - Richtel, Matt (Periódicos Brasil. Pesquisa Científica, 2022)
On a rainy Thursday evening last spring, a 15-year-old girl was rushed by her parents to the emergency department at Boston Children’s Hospital. She had marks on both wrists from self-harm and a recent suicide attempt, and earlier that day she confided to her pediatrician that she planned to try again. At the E.R., a doctor examined her and explained to her parents that she was not safe to go home. “But I need to be honest with you about what’s likely to unfold,” the doctor added. The best place for adolescents in distress was not a hospital but an inpatient treatment center, where individual and group therapy would be provided in a calmer, communal setting, to stabilize the teens and ease them back to real life. But there were no openings in any of the treatment centers in the region, the doctor said. Indeed, 15 other adolescents — all in precarious mental condition — were already housed in the hospital’s emergency department, sleeping in exam rooms night after night, waiting for an opening. The average wait for a spot in a treatment program was 10 days. The girl, being identified by her middle initial, G, to protect her privacy, spent the first week of her wait in a “psych-safe” room in the emergency department. Any equipment that might be used for harm had been removed. She was forbidden to use electronics — to keep her from searching the internet for ways to commit suicide or asking a friend to smuggle in a sharp object, as teens before her had done. Her door was kept open night and day so she could be monitored. It was “padded, insane-asylum-like,” she recalled recently in an interview. “Just walls — all you see is walls.” She grew “catatonic,” her mother recalled. “In this process of boarding we broke her worse than ever.” G’s story describes one of its starkest manifestations of the crisis. Across the country, hospital emergency departments have become boarding wards for teenagers who pose too great a risk to themselves or others to go home. They have nowhere else to go; even as the crisis has intensified, the medical system has failed to keep up, and options for inpatient and intensive outpatient psychiatric treatment have eroded sharply. Nationally, the number of residential treatment facilities for people under the age of 18 fell to 592 in 2020 from 848 in 2012, a 30 percent decline, according to the most recent federal government survey. The decline is partly a result of well-intentioned policy changes that did not foresee a surge in mental-health cases. Social-distancing rules and labor shortages during the pandemic have eliminated additional treatment centers and beds, experts say. Absent that option, emergency rooms have taken up the slack. A recent study of 88 pediatric hospitals around the country found that 87 of them regularly board children and adolescents overnight in the E.R. On average, any given hospital saw four boarders per day, with an average stay of 48 hours. “There is a pediatric pandemic of mental health boarding,” said Dr. JoAnna K. Leyenaar, a pediatrician at Dartmouth-Hitchcock Medical Center and the study’s lead author. In an interview, she extrapolated from her research and other data to estimate that at least 1,000 young people, and perhaps as many as 5,000, board each night in the nation’s 4,000 emergency departments. “We have a national crisis,” Dr. Leyenaar said. This trend runs far afoul of the recommended best practices established by the Joint Commission, a nonprofit organization that helps set national health care policy. According to the standard, adolescents who come to the E.R. for mental health reasons should stay there no longer than four hours, as an extended stay can risk patient safety, delay treatment and divert resources from other emergencies. Yet in 2021, the average adolescent boarding in the E.R. at Boston Children’s Hospital spent nine days waiting for an inpatient bed, up from three and a half days in 2019; at Children’s Hospital Colorado in Aurora in 2021, the average wait was eight days, and at Connecticut Children’s Medical Center in Hartford, it was six. Emergency-department boarding has risen at small, rural hospitals, too, with “no pediatric or mental health specialists,” said Dr. Christian Pulcini, a pediatrician in Vermont who has studied the trend in the state. “There is one clear conclusion,” he told the Vermont legislature recently. “The E.D. is not the appropriate setting for children to get comprehensive, acute mental health services.” Doctors and hospital officials emphasize that adolescents should absolutely continue to come to the E.R. in a psychiatric emergency. Still, many emergency-room doctors and nurses, trained to treat broken bones, pneumonia and other corporeal challenges, said the ideal solution was more preventive care and community treatment programs. “Frankly speaking, the E.D. is one of the worst places for a kid in mental health crisis to be,” said Dr. Kevin Carney, a pediatric emergency room doctor at Children’s Hospital Colorado. “I feel at a loss for how to help these kids.”